Platelet-functionalized three-dimensional poly-ε-caprolactone fibrous scaffold prepared using centrifugal spinning for delivery of growth factors - Rampichová, Michala; Buzgo, Matej; Míčková, Andrea; Vocetková, Karolína; Sovková, Věra; Lukášová, Věra; Filová, Eva; Rustichelli, Franco; Amler, Evžen (International journal of nanomedicine, 2017)
Bone and cartilage are tissues of a three-dimensional (3D) nature. Therefore, scaffolds for their regeneration should support cell infiltration and growth in all 3 dimensions. To fulfill such a requirement, the materials should possess large, open pores. Centrifugal spinning is a simple method for producing 3D fibrous scaffolds with large and interconnected pores. However, the process of bone regeneration is rather complex and requires additional stimulation by active molecules. In the current study, we introduced a simple composite scaffold based on platelet adhesion to poly-ε-caprolactone 3D fibers. Platelets were used as a natural source of growth factors and cytokines active in the tissue repair process. By immobilization in the fibrous scaffolds, their bioavailability was prolonged. The biological evaluation of the proposed system in the MG-63 model showed improved metabolic activity, proliferation and alkaline phosphatase activity in comparison to nonfunctionalized fibrous scaffold. In addition, the response of cells was dose dependent with improved biocompatibility with increasing platelet concentration. The results demonstrated the suitability of the system for bone tissue.
Keywords: Tissue Engineering; tvar buňky; Cell Line, Tumor; Cell Proliferation; osteogeneze; osteoblasty; adhezivita trombocytů; Alkaline Phosphatase; Blood Platelets; Osteoblasts; Platelet Adhesiveness; alkalická fosfatasa; tkáňové inženýrství; 3D scaffold; Drug Delivery Systems; trombocyty; kinetika; Animals; Intercellular Signaling Peptides and Proteins; lidé; PCL; mezibuněčné signální peptidy a proteiny; Humans; zvířata; growth factors; Tissue Scaffolds; proliferace buněk; platelets; Polyesters; cytokines; tkáňové podpůrné struktury; Osteogenesis; nádorové buněčné linie; Cell Shape; Kinetics; lékové transportní systémy; polyestery; centrifugal spinning